EUROJUST AND EPPO ON THE CROSSROADS OF THEIR FUTURE COOPERATION (EU and comparative law issues and challenges series (ECLIC), 2019)
On 19 June 2018, the Bulgarian Presidency of the Council, the European Parliament, and the European Commission agreed on the new Eurojust Regulation. The EU ambassadors confirmed the agreement on 20 June 2018 followed by final adoption of the Regulation in November 2018. This paper refers to the novelties introduced by the new Regulation as well as to the projection of relations between agencies after the finalization of OLAF and EPPO competencies. The authors are analysing current modalities for their cooperation on institutional, operational and administrative levels. Will Eurojust become obsolete and possibly a department in the European Public Prosecutor’s Office or two differentiated bodies that have a future with separated competencies, independent of each other? What role will OLAF play in relation to both agencies, and what impacts will this have on national criminal justice systems? The authors analyse possible scenarios and point to perceived overlapping in competencies.